SKRINING FITOKIMIA DAN UJI SUN PROTECTION FACTOR (SPF) EKSTRAK DAUN KACA PIRING (GARDENIA AUGUSTA L ) SECARA IN VITRO - Yani, Dwi Fitri; Anggraini, Puspita; Apriliani, Rindy (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2025)
The glass plate plant (Gardenia augusta L.) is a medicinal plant with potential applications in traditional medicine. The parts commonly utilized as herbal remedies include the roots, leaves, and mature flower fruits. This study aimed to identify the phytochemical constituents and determine the Sun Protecting Factor (SPF) values of glass plate leaf extract as a natural sunscreen agent. The research methods included extraction using the maceration method, phytochemical screening, and SPF determination using UV–Visible spectrophotometry. The phytochemical test results indicated that the leaf extract of Gardenia augusta L. contained alkaloids, flavonoids, and tannins. The SPF values increased with higher extract concentrations. The SPF values obtained were 10.25, 11.40, 13.14, 17.67, and 24.11 at extract concentrations of 1:30, 1:25, 1:20, 1:15, and 1:10, respectively. Based on the SPF classification, the extract exhibited maximum to ultra protection levels, indicating its potential to be developed as an active ingredient in natural sunscreen formulations.